RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN BERBASIS ANDROID DI SD NEGERI LEREP 04 DI BAGIAN PEMINJAMAN (Information Technology and Telematics, 2015)
Abstract - The school library is a library that serves the students, teachers and employees of a particular school. The school library was established to support the achievement of the objectives of the school, the education and teaching as outlined in the school curriculum. Lerep Elementary School Library System 04 has been using a manual system that has a lot of weaknesses, namely recording transactions peminjanan slow or returning books, borrowers have to queue up in front of the counter and making reports which takes a long time.  The objectives to be achieved is to make android-based library information system in primary schools Lerep 04 at the lending that can handle the problems faced by the State Library Lerep SD 04.Results of this research is the creation of a library information system based on Android at SD Negeri 04 Lerep created using PHP and MySQL and android used as a launcher in running android-based library information system in primary schools Lerep 04. Keywords - Library, SD Negeri Lerep 04, Android